Comparison of phenoloxidase isozymes from two color varieties of Tenebrio molitor L - HUANG Qiong; HU Jie; ZHOU Ding-gang; GOU Lin (浙江大学学报. 农业与生命科学版)
In order to provide some references for studying the body-color diversity, immune defence and variety selection of Tenebrio molitor, the phenoloxidase (including monophenol oxidase and diphenol oxidase) isozyme zymograms and activity at different developmental stages of the yellow - and black-color varieties of T. molitor were compared using vertical polyacrylamide gel electrophoresis and spectrophotometry. The results showed that, during their developmental stages, six monophenol oxidase (MPO) bands and five diphenol oxidase (DPO) bands with different mobility were found, in which the MPO bands were distributed in three zones, while the DPO bands were in two zones. Meanwhile, the eggs of the black-color variety showed one more distinctive MPO bands compared with those of the yellow-color variety. Moreover, the MPO and DPO activities of black-color variety eggs, larvae and adults were significantly higher than those of the yellow-color ones. But at the pupal stage, the MPO activity of the yellow-color variety was higher than that of the black-color one, while the DPO activity was opposite. Distinctive variations were shown in the band numbers, migration rate of enzyme bands and strength of enzymatic activity of MPO and DPO at different developmental stages of both color varieties. Compared with other developmental stages, there was one MPO and one DPO characteristic enzyme band at egg stage of both color varieties, but only one typical DPO band at larval stage. Meanwhile, there was different change on the zymograms and the activities of MPO and DPO of both color varieties at different developmental stages. From the egg to adult stage of both color varieties, the MPO activity changed in the descending order of egg stage > pupal stage > adult stage > larval stage, while the DPO activity varied in the descending order of larval stage > adult stage > pupal stage > egg stage. The results above lay a theoretical foundation for further research on the body-color diversity, immune defence and variety selection of T. molitor.